IMPORTANT FACTORS AND EFFICIENCY OF USING COMMUNICATIVE METHODOLOGY IN THE PROCESS OF TEACHING A FOREIGN LANGUAGE, TOGETHER WITH THE CRITERIA OF PROFESSIONAL COMMUNICATIVE EFFECTIVENESS (Conference Zone, 2022)
This article is about the effectiveness of learning a foreign language using the communicative methodology to organize the process of formation of professional communicative competence together with the criteria for the formation of professional communicative competence.